Immunization against neonatal tetanus in New Guinea: 4. Comparison of tetanus antitoxin titres abtained by haemagglutination and toxin neutralization in mice - Hardegree, M. Carolyn (1970)
Haemagglutination (HA) has been used frequently for the titration of tetanus antitoxin but published results have varied in relation to the ”unitage” determined by the mouse toxin-neutralization test (TN). This report gives the results of the titration of a group of sera by haemagglutination and compares them with the results obtained by toxin neutralization. Although there was marked variation between HA and TN titres of individual sera, results indicated that haemagglutination is a useful procedure for the over-all evaluation of the antitoxin responses to tetanus toxoids in field studies.